2018
DOI: 10.1002/ange.201711643
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Free Enzyme Activity: Quick, High‐Yielding Mechanoenzymatic Hydrolysis of Cellulose into Glucose

Abstract: Mechanochemistry enables enzymatic cleavage of cellulose into glucose without bulk solvents,a cids,o ther aggressive reagents,o rs ubstrate pre-treatment. This clean mechanoenzymatic process (coined RAging) is also directly applicable to biomass,avoids many limitations associated with the use of cellulases,a nd produces glucose concentrations greater than three times that obtained by conventional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…Furthermore, the absence of solventt ranslates into am uch smaller total reaction volume, which facilitates manipulation while generating less waste, and enables reactions of poorly soluble and recalcitrant substrates such as chitin and cellulose. [46] These advances may offer cost-effective sustainable strategies to transform waste into useful chemicals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the absence of solventt ranslates into am uch smaller total reaction volume, which facilitates manipulation while generating less waste, and enables reactions of poorly soluble and recalcitrant substrates such as chitin and cellulose. [46] These advances may offer cost-effective sustainable strategies to transform waste into useful chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Water is an essential substrate for chitinase activity and was also used as the liquid additive in LAG. [34,38,46] The amount of water in LAG was optimized by varying the ratio of liquid volumetot he weightoft he reaction mixture (h) [34][35][36] from 0t oa pproximately 3 mLmg À1 ,w hich revealed that the yield reached ap lateaua th % 1.7 mLmg À1 (i.e., 500 mLw ater per 300 mg reaction mixture;F igure 2A). [56] Such water loading is consistent with LAG conditions previously reported in mechanochemical reactions [34][35][36] and produces a moist solid-an initial texture that was also optimal for the hydrolysis of cellulose by cellulases through RAging ( Figure S6 in the SupportingI nformation).…”
Section: Enzymatic Activity Is Enhanced Under Mechanochemical Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35,36] In this regard, the stability of enzymes under mechanical stress has been confirmed using continuous grinding processes or mechanochemical activation followed by static incubation (RAging) with excellent results. [37,38] Nevertheless, no detailed information concerning the effect of milling on the degree of denaturation, the parameters and conditions affecting enzyme efficiency, or changes in the structure of CALB have been disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…Thes tructure of K 2 FeO 4 solid was characterized with X-ray diffraction ( Figure S3), scanning and transmission electron microscopy (SEM and TEM), revealing that the purple-black crystalline powder was composed of large plate crystals on the scale of several to dozens of mm( Figures 1b,S 4). Fors olid-state reactions of such crystalline oxidizer,t he reactivity is predefined by the exposed facets.S elected area electron diffraction (SAED) patterns were obtained on ferrate(VI) for the first time,which confirmed the single-crystalline nature of the individual plates and disclosed that K 2 FeO 4 crystals predominantly exposed the low-index {001} planes (top and bottom facets) with side planes of {200} and {010} jointed by small {210}, as shown in Figure 1c.Considering its large crystal size and that crystal particles preferentially expose the planes with low surface energy (and expected low reactivity), [13] such as the {001} planes of K 2 FeO 4 ,mechanical milling was employed to crush the original crystals and continually generate reactive fracture surface to participate into redox reactions.A nother merit of mechanochemistry is the ability to promote reactions under solvent-free conditions, [14] which is particularly beneficial for reactants like K 2 FeO 4 that lack solubility in media.…”
mentioning
confidence: 99%